Sunlight-Driven Biomass Photorefinery for Coproduction of Sustainable Hydrogen and Value-Added Biochemicals - Wu, Xinxing; Zhao, Heng; Khan, Mohd Adnan; Maity, Partha; Al-Attas, Tareq; Larter, Stephen; Yong, Qiang; Mohammed, Omar F.; Kibria, Md Golam; Hu, Jinguang (ACS sustainable chemistry & engineering, 2020)
We demonstrate a potential pathway of biomass photorefinery (PR) using low-cost CoO/g-C₃N₄ catalysts for the coproduction of hydrogen and lactic acid under visible light illumination. To do so, we follow a bottom-up approach to systematically investigate the photoreforming performance of glucose, different model celluloses (cellulose I and mercerized and regenerated cellulose II), and raw biomass. Under optimized conditions, the glucose was totally consumed within 3 h of reaction, with nearly 78 wt % carbon conversion to lactic acid. The highest activity observed for cellulose in the PR used phosphoric acid swollen cellulose (PASC, regenerated cellulose II) with a H₂ production rate of ∼178 μmol·h–¹·gcₐₜ–¹, more than 71 wt % cellulose conversion after 12 h, and the formation of ∼617 μmol lactic acid per gram of cellulose. This high activity was mainly attributed to enhanced interaction of the photocatalyst with PASC, as evidenced by quartz crystal microbalance analysis. Based on the knowledge obtained from model cellulose, we took a step further to evaluate the photorefining ability of raw lignocellulosic biomass wheat straw (WS), with/without various biomass pretreatment strategies. The pretreated biomass showed much higher H₂ and lactic acid production and cellulose conversions as compared with raw biomass but the degree of improvement is highly dependent on pretreatment strategies. Our results not only demonstrate the potential of using visible light for the coproduction of H₂, along with value-added bioproducts from biomass PR, but also shed light on developing pretreatment strategies to achieve a scalable biomass PR.